Uma História Severina - Diniz, Debora; Brum, Eliane (Brazil : Paranhos, Fabiana, 2005)
Severina had her destiny changed by a Supreme Court decision. Four months pregnant with an anencephalic fetus, she was in the hospital at the very moment the Supreme Court cancelled the authorization to interrupt the pregnancy. It was October 20, 2004. Severina, a farmer from the small city of Chã Grande – Brazil, wife of Rosivaldo and mother of Walmir, spent three months going from courts to hospitals and back to courts, trying to find someone who would help her to stop all that suffering. The documentary put her tragic story on the screen, telling about the long “day after” that the judges of the Supreme Court never witnessed.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films